Atmosphere Versus Weather Prediction - Santos, Isimar de Azevedo; Buchmann, Julio (Anuário do Instituto de Geociências, 2011)
The present work deals with the controversy between the human understanding of the behavior of real atmosphere and the weather prediction in response to numerical models. Themes like the Chaos Theory, Eulerian and Lagrangian models, and atmospheric waves are considered, reviewed and criticized.